Utility of synthetic MRI in predicting pathological complete response of various breast cancer subtypes prior to neoadjuvant chemotherapy. Issue 11 (November 2022) - Matsuda, M.; Fukuyama, N.; Matsuda, T.; Kikuchi, S.; Shiraishi, Y.; Takimoto, Y.; Kamei, Y.; Kurata, M.; Kitazawa, R.; Kido, T.
Abstract : AIM: To evaluate the usefulness of synthetic magnetic resonance imaging (MRI) performed before the initiation of neoadjuvant chemotherapy (NAC) in predicting whether breast cancers can achieve a pathological complete response (pCR) after the completion of NAC. MATERIALS AND METHODS: This retrospective study investigated 37 consecutive patients with 39 breast cancers (pCR: 14, and non-pCR: 25) who underwent dynamic contrast-enhanced (DCE)-MRI and synthetic MRI before the initiation of NAC. Using synthetic MRI images, quantitative values (T1 and T2 relaxation times, proton density [PD] and their standard deviations [SD]) were obtained in breast lesions, before (Pre-T1, Pre-T2, Pre-PD, SD of Pre-T1, SD of Pre-T2, SD of Pre-PD) and after (Gd-T1, Gd-T2, Gd-PD, SD of Gd-T1, SD of Gd-T2, SD of Gd-PD) contrast agent injection. The aforementioned quantitative values and several morphological features that were identified on DCE-MRI were compared between pCR and non-pCR. RESULTS: Multivariate analyses revealed that the SD of Pre-T2 ( p= 0.038) was significant and was an independent predictor of pCR, with an area under the receiver operating characteristics curve of 0.829. The sensitivity, specificity, and accuracy of the SD of Pre-T2 with an optimal cut-off value of 11.5 were 71.4%, 80%, and 76.3%, respectively. CONCLUSIONS: The SD of Pre-T2 obtained from synthetic MRI was used successfully to predict those breast cancers that would achieve a pCR after the completion of NAC; however, these results are preliminary and need to be verified by further studies. Highlights: Accurately predicting tumour response to NAC in breast cancer is crucial. Synthetic MRI can obtain some quantitative values during a single scan. SD of T2-Pre of breast cancer was successfully used to predict pCR prior to NAC.